Kinetics and Mechanism of Oxidation of Hexamethylenediaminetetraacetatocobaltate(II) Complex by Periodate Ion in Aqueous Medium - R. M. Naik; B. Kumar J. Rai; R. Rastogi; S. B. S. Yadav (E-Journal of Chemistry)
The kinetics and mechanism of oxidation of [CoII HDTA]4- (Where HDTA=Hexamethylenediamine tetraacetic acid} by periodate ion has been studied in aqueous acidic medium. The reactions has been investigated spectrophotometrically at λmax = 580 nm under pseudo- first -order condition by taking large excess of oxidant [IO4] at pH = 4.0±0.02, I = 0.1 M (CH3COONa + NaNO3).and temperature = 30± 0.1 °C The electron transfer reaction between [CoII HDTA] 4- and [IO4-] obeys inner sphere reaction pathway through the formation of long-lived intermediate complex which finally get converted into a corresponding [CoIIIHDTA] 3- complex as final reaction product. The experimental observations have shown that the reaction obey first- order dependence in [CoII HDTA] 4--. The variation of pseudo-first-order rate constants (kobs) with[IO4-], keeping other reaction variables fixed at constant value was found to obey the rate law: kobs=a[IO4-]2/b+c[IO4-], which is consistent with a three step mechanistic scheme. The values of kobs are almost constant with increasing pH, which can be attributed to the reaction of deprotonated form of [CoIII HDTA] 4- complex only, in the entire pH region. Eyring’s equation has been used to calculate the thermal or activation parameters and found to be, ΔH# = 28.69 kJ mole–1; ΔS# = – 481.13 J K-1 mole–1 respectively and support the proposed mechanistic scheme.